Lutas diuturnas: políticas públicas, patrimônio e o reconhecimento do clube social negro 24 de Agosto na cidade de Jaguarão (RS) - Alexandre Peres de Lima (Ciências Sociais Unisinos)
he article discusses heritage as a result of the complex articulation of the struggles of Clube 24 de Agosto, a black social club in Jaguarão, a town located at Brazil’s border with Uruguay, as well as the developments that led to the club’s recognition as a historical and cultural heritage of the state of Rio Grande do Sul in 2012. On the basis of an ethnographic survey conducted between 2013 and 2015, I articulate the following plot: I describe the formation of a regional public sphere of black social clubs denouncing judicial discretion in favor of a particular administrative police, viz ECAD. This institution is the trigger for the struggles of the participants of Clube 24 de Agosto in their search for public poli-cies for the preservation of their cultural and historical space. On this path they face institutional racism and disregard at the local level. A public sphere of mobilization and denunciation in favor of the demands of the club for protection is established in this context. The club’s recognition as a heritage involves a series of problems and distortions that ignore its autonomy. However, the positive impacts of this empowerment make the club an example to think about the “politics of otherness” that breaks the invisibility and gains recognition, which is a condition that leads subjects to self-respect. The article’s goal, based on this articulation, is to show the affirmative powers and mobilization through public denunciations by the participants of the club and their politically mobilized allies against a number of institutional devices of disregard for their demands and the profound effects achieved by their struggle.